The Influence of blood pressure on the outcome of acute ischemic stroke in patients treated with thrombolytic therapy and mechanical thrombectomy: - - Ninković, Aleksandar (Medicinski podmladak, 2025)
Introduction: Acute stroke is one of the most common causes of death in the world and the first cause of disability in the developed countries. An acute ischemic stroke (AIS) occurs as a result of cerebral circulation disorders due to occlusion of a blood vessel either by thrombosis or embolism. Modern therapy aims to prevent the penumbra cells’ death by reestablishing the blood flow, which can be performed using a pharmaceutical or endovascular interventions. It is recommended to reduce and maintain the patients’ blood pressure below 185/110 mmHg before and during the application of thrombolysis, as well as to maintain the same blood pressure value regarding mechanical thrombectomy application, and below 180/105 mmHg 24 hours after the applicaton of thrombolysis. Aim: The aim of the study was to determine the causality between blood pressure below 170 mmHg in patients treated with thrombolytic therapy, mechanical thrombectomy and both methods, and a more favorable outcome of AIS. Material and methods: The work is based on research and retrospective analysis of data collected at the Neurology Clinic of the Clinical Center of Vojvodina and refers to 103 patients with AIS who were treated with thrombolytic therapy, mechanical thrombectomy or both methods, in the period from January 1st to December 31st, 2023. Results: Median patient National Institute of Health Stroke Scale (NIHSS) scores for systolic pressure ≤170 mmHg and >170 mmHg for all groups combined (U=278.50; p=0.21), for the thrombolysis group (U=111.00; p=0.58), and for the thrombolysis/thrombectomy group (U=15.20; p=0.20) are not statistically significantly different, while their difference for the thrombectomy group cannot be calculated. Conclusion: Systolic pressure below 170 mmHg 24 hours after any of the therapeutic procedures is not associated with a more favorable outcome of AIS, therefore it is not necessary to strictly control it more than one day after the conclusion of one of those.